Kajian komoditi pemicu inflasi di Kota Jambi - Junaidi Junaidi; Tona Aurora Lubis (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2015)
This study aims to analyze: 1) developments and fluctuations in inflation in Jambi City; 2) commodities which are the trigger factors for inflation in Jambi City. The main and supporting data used are sourced from the Central Statistics Agency, Bank Indonesia and the Jambi City Bappeda. Data analysis was carried out descriptively analytic. The results of the study found: 1) During 2015 (until September), Jambi City experienced a deflation of -0.08 percent (y-t-d). This shows the success of Jambi City in controlling the inflation rate; 2) foodstuffs group is the biggest contributor to inflation and deflation in Jambi City; 3) the main commodity that triggers inflation in Jambi City is an increase in food ingredients (inflation food) in addition to administered inflation factors (increases in government-regulated price components such as fuel prices, electricity tariffs, transport fares and others). Therefore, price movements are predominantly determined by an increase in demand that usually occurs on religious holidays, and by movements in the supply of these foods.